Penyuluhan Kesehatan serta Pemeriksaan Kadar Hemoglobin dan Protein Urin pada Remaja Putri - Heri Setiyo Bekti; I Gusti Agung Ayu Dharmawati; Ida Bagus Oka Suyasa (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Adolescence is an age stage that comes after childhood ends which is characterized by rapid growth with an age range of 10-19 years. Teenage girls are generally more prone to anemia than teenage boys. This community service activity aims to provide education to teenage girls about anemia and laboratory tests such as Hb levels and urine protein as an effort to provide health services to teenage girls at SMPN 1 Ubud, Gianyar. The method of implementing this activity includes counseling about anemia, checking Hb levels, and urine protein examination, as well as pre-test and post-test to determine the level of knowledge of teenage girls about anemia. From the results of the examination of 34 respondents, it was found that 29.4% had anemia and none of the respondents had proteinuria. As many as 94% of respondents have a good level of knowledge about anemia. There needs to be a role from family, school, and government to improve the health status of teenage girls such as giving blood tablets regularly to avoid anemia.